The Quality of Sentence Translation Realized as Face-Threatening Speech in the Wolf Totem Novel - Supriadi, Nunung; Setiajid, Harris Hermansyah; Zain, Adella Amira (Faculty of Humanities, Universitas Jenderal Soedirman, 2025)
Translated novels are an important tool for Indonesian readers to find out the complete contents of novels in foreign languages, one of which is Chinese novels. The purpose of this study was to determine the translation quality of face-threatening utterances in the Wolf Totem novel so that it is easier for Indonesian readers to understand the contents of the novel holistically. The research method used in this research is descriptive qualitative (Santoso, 2021; Arikunto, 2009; Saebani, 2008; Creswell, 2007) using a pragmatic approach to face-threatening speech act (Brown and Levinson, 1987; Austin, 1962; Searle , 1969; Djatmika et al, 2016). Translation theory is used to analyze translation techniques used to measure the quality of translation in terms of accuracy, acceptability, and readability (Nababan, 2003; Nababan et al, 2012; Molina and Albir, 2002; Newmark, 1988; Catford, 1965) . The findings in this study are the use of discursive creation techniques as much as 53%, with the accuracy level of 53%, the acceptability level 91%, and readability level of 94%.